Group decision and negotiation : theory, empirical evidence, and application : 16th International Conference, GDN 2016, Bellingham, WA, USA, June 20-24, 2016, revised selected papers - Bajwa, Deepinder; Koeszegi, Sabine T.; Vetschera, Rudolf (Springer, 2017)
This book constitutes revised selected papers from the 16th International Conference on Group Decision and Negotiation, GDN 2016, held in Bellingham, WA, USA, in June 2016. The GDN meetings aim to bring together researchers and practitioners from a wide spectrum of fields, including economics, management, computer science, engineering, and decision science. The 12 papers presented in this volume were carefully reviewed and selected from 70 submissions. They deal with the fundamental part of all decision processes and individual preferences; the situations of group decision making; the collective decision making in situations characterized by a higher level of conflict; and the group processes and negotiations in different subject areas.
Keywords: Group decision making -- Congresses.; Operations research.; Decision making.; Management information systems.; Application software.; Game theory.; elektronické knihy; electronic books